1971
DOI: 10.1002/bjs.1800580503
|View full text |Cite
|
Sign up to set email alerts
|

A bacteriological study of the immediate environment of a surgical wound

Abstract: In an attempt to assess the importance of different aspects of the immediate wound environment during an operation, detailed bacteriological data were obtained in the operating theatre from 1000 patients operated upon in two different theatres.Nasal and skin carriage of Staphylococcus pyogenes were found to be associated with a small number of autogenous infections, but no significant increase in the staphylococcal wound infection incidence could be shown in these groups. Skin carriage of other pathogens seeme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0
1

Year Published

1971
1971
2005
2005

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 46 publications
3
8
0
1
Order By: Relevance
“…and Klebsiella spp. [12–14]. The present study confirmed that these pathogens were the main causative pathogens of wound infections, but other nosocomial microorganisms were also cultured from all seven wound infections.…”
Section: Microorganisms Isolated From Wounds Following Elective Open supporting
confidence: 79%
“…and Klebsiella spp. [12–14]. The present study confirmed that these pathogens were the main causative pathogens of wound infections, but other nosocomial microorganisms were also cultured from all seven wound infections.…”
Section: Microorganisms Isolated From Wounds Following Elective Open supporting
confidence: 79%
“…The number of bacteria present varies according to the type of operation and its duration (Davidson, Smith and Smylie, 1971;Gilmore and Sanderson, 1975). In 'clean' cases (when no hollow viscus is incised) of short duration, the inoculum is usually sub-infective.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of airborne contamination in wound infection is open to debate (5,14,15,17). In the operating conditions of New York in 1901 the incidence of postoperative wound infection in clean cases was only 3.2% (9), and other studies have found that the pathogenic organisms in post-operative wound infections are those found in ward air or shed from medical and nursing staff (10).…”
Section: Belizean Civilian Practicementioning
confidence: 99%